Organización del capítulo fructífero y heterocarpia en Bidens pilosa L. - Marinis, G. de. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Bidens pilosa L.. (Compositae) one among the World's worst weeds, produces open globose heads of desmochorous achenes disposed radially around the receptacle. These achenes are more numerous (about 60%) in the inferior hemisphere and their length decreases, while their width increases, along an apex — basis gradient. The achenes nearer to the basis (about 20%) are much shorter and differ from the others also in shape and in ornamentations. These brachycamous achenes remain connected to the receptacle longer than the other ones and showed a very low percentage of germination, in common laboratory conditions. B. pilosa, therefore, shows a certain degree of heterocarpy, perhaps associated with the process of dispersal and germina-tion of its achenes.